The accuracy of using vergence formula to screen myopia in children: a cross-sectional study - Yi, Zhen; Hong, Chang; Haikuo, Huang; Xinxin, Wang (Frontiers in Medicine, 2023)
Objective To evaluate the accuracy of using the vergence formula to screen myopia in children and adolescents. Methods This was a cross-sectional study conducted between December 2022 and May 2023 at the ophthalmology clinic of Beijing Tongren Hospital. A total of 336 children aged 6 to 12 years with refractive errors were selected according to the inclusion criteria. Biometric measurements, including axial length, corneal thickness, anterior chamber depth, corneal curvature, and lens thickness, were obtained using a biometer. The Calculated spherical equivalent (SE) was then calculated using the vergence formula. Cycloplegic refraction was performed after paralysis of the ciliary muscle, and the subjective SE was recorded. A diagnosis of myopia was made if the subjective SE was ≤ −0.50 diopters. Results The AL/CR, subjective SE, and calculated SE were not normally distributed (p < 0.05). The AL/CR value was 3.08 (2.81, 3.27), the SE was −1.60 D (−6.00 D, 3.75 D), and the calculated SE was −1.42 D (−6.64 D, 5.73 D). There was no significant difference between the calculated SE and the SE (Z = −2.899, p = 0.004). The AL/CR value was negatively correlated with SE (r = −0.687, p < 0.01), and the calculated SE was positively correlated with SE (r = 0.827, p < 0.01). The area under the ROC curve for predicting myopia using AL/CR and calculated SE was 0.876 and 0.962, respectively, and the difference between the two was significant (p < 0.001). The sensitivity of AL/CR was 84.2%, the specificity was 70.6%, the accuracy was 82.1%, and the Youden index was 0.548. The sensitivity of calculated SE was 83.1%, the specificity was 100%, the accuracy was 85.7%, and the Youden index was 0.831. Conclusion The vergence formula can be used to evaluate myopia in children and adolescents with relatively high accuracy without cycloplegic refraction.